Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ma15103709
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Zirconium, Titanium and Strontium on the Properties and Microstructure of AlSi7Mg0.3Cu0.5 Alloy

Abstract: The aim of the paper is to describe and specify the properties and microstructure of Al-Si alloy using Zr, a combination of Zr with elements used in the grafting of Al (Ti) alloys, and modification (Sr). Al-Si alloys with a combination of Zr and Ti and Sr elements represent an opportunity for the development of new aluminum alloys with a specific use. The experiment focused on the analysis of the synergistic effects of Zr with Ti and Zr with Sr on a AlSi7Mg0.3Cu0.5 alloy. The experimental alloys contained a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The data in the technical literature [8][9][10][11][12] shows that zirconium (Zr) in aluminium alloys for plastic working inhibits the grain growth, allowing in this way for high electrical and mechanical properties to be obtained in the alloys. This is also the reason why zirconium is sometimes used as a modifier.…”
Section: Introductionmentioning
confidence: 99%
“…The data in the technical literature [8][9][10][11][12] shows that zirconium (Zr) in aluminium alloys for plastic working inhibits the grain growth, allowing in this way for high electrical and mechanical properties to be obtained in the alloys. This is also the reason why zirconium is sometimes used as a modifier.…”
Section: Introductionmentioning
confidence: 99%
“…Some variants of the thermal methods developed recently, based on intensive cooling of the mould, can alleviate some of these problems [8,9]. However, use of inoculants is a much more efficient and less energy intensive way to improve the material properties at relatively low cost and in a sustainable manner [10][11][12][13]. If the amount of inoculant remains low, it may have negligible effect on a chemical composition, but it can significantly influence the grain size and the microstructure, leading to significant improvements in the mechanical and tribological properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we should note the study of Yu Zhang et al [11], who observed that a copper addition to the concentration within the range of 0.8% to 2.0% makes the eutectic phase α Mg + γ(Mg 17 Al 12 ) better ordered, and its arrangement becomes totally dendritic. Despite some interest in the inoculant effect on magnesium alloys [10][11][12][13][14][15][16][17][18][19] the mechanism of interactions and their effect are not fully understood.…”
Section: Introductionmentioning
confidence: 99%